Prospective study of proton‐beam radiation therapy for limited‐stage small cell lung cancer. Issue 21 (5th July 2017) - Rwigema, Jean‐Claude M.; Verma, Vivek; Lin, Liyong; Berman, Abigail T.; Levin, William P.; Evans, Tracey L.; Aggarwal, Charu; Rengan, Ramesh; Langer, Corey; Cohen, Roger B.; Simone, Charles B.
Abstract : BACKGROUND: Existing data supporting the use of proton‐beam therapy (PBT) for limited‐stage small cell lung cancer (LS‐SCLC) are limited to a single 6‐patient case series. This is the first prospective study to evaluate clinical outcomes and toxicities of PBT for LS‐SCLC. METHODS: This study prospectively analyzed patients with primary, nonrecurrent LS‐SCLC definitively treated with PBT and concurrent chemotherapy from 2011 to 2016. Clinical backup intensity‐modulated radiotherapy (IMRT) plans were generated for each patient and were compared with PBT plans. Outcome measures included local control (LC), recurrence‐free survival (RFS), and overall survival (OS) rates and toxicities. RESULTS: Thirty consecutive patients were enrolled and evaluated. The median dose was 63.9 cobalt gray equivalents (range, 45‐66.6 cobalt gray equivalents) in 33 to 37 fractions delivered daily (n = 18 [60.0%]) or twice daily (n = 12 [40.0%]). The concurrent chemotherapy was cisplatin/etoposide (n = 21 [70.0%]) or carboplatin/etoposide (n = 9 [30.0%]). In comparison with the backup IMRT plans, PBT allowed statistically significant reductions in the cord, heart, and lung mean doses and the volume receiving at least 5 Gy but not in the esophagus mean dose or the lung volume receiving at least 20 Gy. At a median follow‐up of 14 months, the 1‐/2‐year LC and RFS rates were 85%/69% and 63%/42%, respectively. The median OS was 28.2 months, and the 1‐/2‐year OS rates were 72%/58%. There was 1 case each (3.3%) of grade 3 or higher esophagitis, pneumonitis, anorexia, and pericardial effusion. Grade 2 pneumonitis and esophagitis were seen in 10.0% and 43.3% of patients, respectively. CONCLUSIONS: In the first prospective registry study and largest analysis to date of PBT for LS‐SCLC, PBT was found to be safe with a limited incidence of high‐grade toxicities. Cancer 2017;123:4244–4251. © 2017 American Cancer Society . Abstract : This first‐ever prospective study evaluates the utility of concurrent chemotherapy and proton‐beam radiation therapy for limited‐stage small cell lung cancer. Proton‐beam radiation therapy decreases cardiac and pulmonary doses (mean/volume receiving at least 5 Gy) in comparison with intensity‐modulated radiotherapy and produces survival and toxicity outcomes that compare favorably with prior reports of conventional photon therapy.